Analisis Pengaruh Tingkat Bagi Hasil Deposito Mudharabah, FDR, Suku Bunga, Inflasi, dan PDB terhadap Jumlah Deposito Mudharabah pada Bank Pembiayaan Rakyat Syari’ah (BPRS) di Provinsi Banten - Shoona Kabila Mahaaba (ISLAMINOMICS: JOURNAL OF ISLAMIC ECONOMICS, BUSINESS AND FINANCE, 2020)
This reseach aims to analyze the variable profit sharing rate of mudharabah deposits, FDR, inflation rates, and GDP in influencing the amount of mudharabah deposits at the Sharia People Financing Bank (BPRS) in Banten Province. The data used in this study are time series data and cross section (panel data) for the first quarterly of 2015 to the fourth quarterly of 2018. Meanwhile, the independent variable used is the profit sharing rate of mudharabah deposits, FDR, interest rates, inflation, and products Gross Domestic and as the dependent variable is the amount of mudharabah deposits. The method used is a quantitative method of panel data with a fixed effect model approach. The results showed that the rate of sharing of mudharabah deposits, FDR, interest rates, inflation, and GDP had a significant effect on the amount of mudharabah deposits simultaneously. But partially, the profit sharing rate of mudharabah deposits has a positive and significant effect on the amount of mudharabah deposits. FDR, interest rates and inflation have a negative and significant effect on the amount of mudharabah deposits. while GDP has a negative and not significant effect on the amount of mudharabah deposits.